“Speedy Biochemistry” as a new teaching method in preclinical curriculum - Noor Akmal Shareela Ismail (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Previous conventional practical session was reported to be less effective in achieving its objectives. Therefore, “Speedy Biochemistry” was introduced to assist students to apply knowledge they have learnt in the classroom. This setting promotes teamwork and application of knowledge in problem solving which can be achieved through active learning. Active learning has piqued the interest of the academic community in giving more benefits to the students. Steps on how to conduct the “Speedy Biochemistry” among Year-1 medical students were illustrated and collection of their feedback was recorded. “Speedy Biochemistry” can be a good active learning session to enhance and improve medical students’interest in learning and their self-learning abilities in Biochemistry.